Thermoacoustic Heat Engine - Mohd. Ghazali, N. (Penerbit UTM Press, 2004)
This paper is an attempt at introducing the latest technology in fluid power, thermoacoustics, a phenomenon due to solid-fluid interactions. Thermoacoustics can be generally characterised by the following two categories. The first, the oscillations induced by temperature difference across a stack of plates can generate acoustic power consistent of a prime mover. While the reverse, that of heat transfers across a stack of plates powered by acoustic waves is typical of a heat pump learnt in the engineering introductory course. Basic thermoacoustic theory and some simple thermoacoustic design parameters that are currently being used are discussed. Analysis using these theories is shown. Discussions through this paper will show the way for initial and continuing research into thermoacoustics, particularly in the experimental and numerical fields.